2022
DOI: 10.1155/2022/2920255
|View full text |Cite
|
Sign up to set email alerts
|

Abbreviated MDS-UPDRS for Remote Monitoring in PD Identified Using Exhaustive Computational Search

Abstract: Background. The Movement Disorder Society Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) comprises 50 items, consisting of historical questions and motor ratings, typically taking around 30 minutes to complete. We sought to identify an abbreviated version that could facilitate use in clinical practice or used remotely via telemedicine. Methods. To create an 8-item version we conducted an “exhaustive search” of all possible subsets. We measured explained variance in comparison to the 50-item version using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…For assessment of motor features of PD, we included: the Hoehn and Yahr scale [9], the Movement Disorders Society-sponsored revision of the Unified Parkinson's Disease Rating Scale (MDS-UPDRS) [10], the remote versions of both the Unified Parkinson's Disease Rating Scale (UPDRS) and the MDS-UPDRS [11][12][13], the UPDRS Gaitaxial score [14], and the Unified Dyskinesia Rating Scale (UDysRS) [15]. We also included scales on motor symptoms flagged as most bothersome by PPIE representatives, namely gait and balance problems (question about falls (e.g., Prevention of Falls Network Earth (ProFaNE) definition of a fall [16]), Mini-Balance Evaluation Systems Test (Mini-BESTest) [17], Berg Balance Scale [18], Falls Efficacy Scale International (FES-I) [19], and Activities-Specific Balance Confidence Scale (ABC Scale) [20]), and speech and swallowing issues (Generic Scale for Dysphagia-Related Outcomes (Quality of Life) (SWAL-QOL) [21][22][23][24], Swallowing Disturbance Questionnaire (SDQ) [25], and Radboud Oral Motor Inventory for Parkinson's Disease (ROMP) [26]).…”
Section: Resultsmentioning
confidence: 99%
“…For assessment of motor features of PD, we included: the Hoehn and Yahr scale [9], the Movement Disorders Society-sponsored revision of the Unified Parkinson's Disease Rating Scale (MDS-UPDRS) [10], the remote versions of both the Unified Parkinson's Disease Rating Scale (UPDRS) and the MDS-UPDRS [11][12][13], the UPDRS Gaitaxial score [14], and the Unified Dyskinesia Rating Scale (UDysRS) [15]. We also included scales on motor symptoms flagged as most bothersome by PPIE representatives, namely gait and balance problems (question about falls (e.g., Prevention of Falls Network Earth (ProFaNE) definition of a fall [16]), Mini-Balance Evaluation Systems Test (Mini-BESTest) [17], Berg Balance Scale [18], Falls Efficacy Scale International (FES-I) [19], and Activities-Specific Balance Confidence Scale (ABC Scale) [20]), and speech and swallowing issues (Generic Scale for Dysphagia-Related Outcomes (Quality of Life) (SWAL-QOL) [21][22][23][24], Swallowing Disturbance Questionnaire (SDQ) [25], and Radboud Oral Motor Inventory for Parkinson's Disease (ROMP) [26]).…”
Section: Resultsmentioning
confidence: 99%
“…In our dataset, every assessment has been recorded and saved in the form of multiple video clips, one video per item. We selected, for activity recognition model training, a subset of items that can be performed without assistance, taking into consideration overall informativeness about a patient's holistic disease state [24]. Some MDS-UPDRS items correspond to two distinct activities, such as left and right hand Finger Tapping.…”
Section: Methodsmentioning
confidence: 99%
“…The inability to examine rigidity remotely represents a major limitation for the assessment of patients with suspected parkinsonism. In these cases, the presence of a physician or another trained healthcare professional at the originating site is of paramount importance [ 47 ]. A study investigating the feasibility of the use of telemedicine for at-home titration in cases of LCIG infusion has demonstrated that most neurologists felt no significant limitations during the virtual evaluation of the patients, compared to hospital in-person assessment, as they could visually estimate postural instability and rigidity during the mobility of the patient [ 48 ].…”
Section: Neurological Examination Via Videoconferencingmentioning
confidence: 99%
“…A recent study using exhaustive computational searching methodology has identified a shortened 8-item version of the MDS-UPDRS with high agreement with the original MDS-UPDRS that can be administered remotely [ 47 ]. In particular, the researchers of this study initially excluded the items of rigidity and retropulsion testing, as well as those that require the inspection of lower limbs (toe tapping, leg agility, gait, freezing of gait, posture, and body bradykinesia), since during remote examination patients usually use a digital device (smartphone, tablet, or computer) placed in front of them on a table or desk [ 47 ]. This proposed abbreviated MDS-UPDRS version for the remote assessment included the following items: 1.13 fatigue, 2.5 dressing, 2.10 tremor, 2.12 walking and balance, 3.2 facial movements, 3.4 finger tapping, 3.9 rising from chair, and 4.3 time spent in the off state [ 47 ].…”
Section: Movement Disorders’ Scales Via Telemedicinementioning
confidence: 99%